A comparative study to analyze the effect of planter fascia stretch and heel pad with moist heat in the patients of planterfascitis - Komal Razzaq; Umair Arif; Iqra Tahir; Touseef-; Asima Liaqat; Kaiynat Shafique; Hafiz Muhammad Almas Sabir (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Background: This study investigated the effect of planter fascia stretch and heel pad with moist heat in the patients of planterfascitis among subjects aged 20-40. Planter fascia is a thickened fibrous sheet of connective tissue which begins from medial tubercle on undersurface of calcaneus and fans out joining to the metatarsophalangeal joints plates to form longitudinal foot arch. Manual active stretching or passive stretching of planter fascia and Achilles tendon are effective treatment option for patient with planter fasciitis. Aims and objectives: objectives of this study were to see the effect of planter fascia stretch and heel pad with moist heat in the patients of planterfascitis.  Material and methodology: This study was quasi experimental study. It took samples by convenient method from 80 subjects among Faisalabad private hospitals community. The study was completed in the duration of 3 months. Data was conducted through convenient sampling from Faisalabad private hospitals. This study explored the effect of planter fascia stretch and heel pad with moist heat on subjects aging 20-40 years old. Subjects were allocated to group A (n=40) and group B (n=40). Group A received treatment as planter fascia stretch and group B received treatment as heel pad with moist heat. Follow up were taken after 4 weeks in 3 month duration study.  Results: Statistical Analysis Data were analyzed using SPSS version 23.0. Intragroup comparison of differences between pre and post intervention scores of FFI and FADI was analyzed using independent T Test. The results were considered statistically significant if p values were less than 0.05). No statistically significant difference was observed in pre intervention score between the groups on FADI (p = 0.211) and FFI (p = 0.365), but, statistically significant difference was observed between all the groups on post intervention score with respect to FADI (p=0.000) and FFI (p=.001) as analyzed by independent t test.  Conclusion: After applying the entire treatments and measuring pre and post value it conducted that planter fascia stretch has more significant effect on planterfascitis than heel pad with moist heat.